Cost‐effectiveness of regular versus irregular supportive periodontal therapy or tooth removal. (5th September 2016) - Schwendicke, Falk; Stolpe, Michael; Plaumann, Anna; Graetz, Christian
Abstract: Aim: For periodontitis patients, regular supportive periodontal therapy (SPT) decreases risks of tooth loss, with savings for tooth replacement possibly compensating SPT‐costs. We aimed to assess the cost‐effectiveness of regular versus irregular SPT, and to compare both strategies with immediate tooth removal. Methods: A private payer perspective within German healthcare was adopted. A tooth‐level Markov model was constructed. Replacement of 50% of removed teeth via implant‐supported crowns was modelled in the base case. Cost‐effectiveness was estimated as Euro/tooth retention year using Monte Carlo microsimulations. Scenario analyses were performed. Results: Regular SPT was more effective (tooth retention 28.7 versus 26.1 years), but more costly (806 versus 731 Euro per tooth), with an incremental cost‐effectiveness ratio (additional costs per tooth retention year) of 29 Euro/year. Regular SPT was less costly if costs for SPT per tooth and visit were <5.03 Euro, patients had high risk of tooth loss, or teeth were regularly replaced. Immediately removing and replacing teeth was usually most costly. Conclusions: Within the chosen healthcare setting and on the basis of current evidence, regular SPT retains teeth longer than irregular SPT, but does not necessarily reduce expenses. Decision‐making should consider the subjective value placed on retaining teeth, the technical feasibility of replacement, and the impact of periodontal on general health.